(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now-a-days we see massive improvement in construction industry and infrastructure development. In India almost all, the metro cities are covered with impermeable concrete pavement that creates an environmental issue, such as decrease of rainwater penetration into the ground. Hence a continuous falls in water table which leads to water disaster during summer. We can overcome the above problem by using permeable concrete. Porous concrete is a special type of concrete, which is normally used for drain the storm water runoff in rainy days. Concrete ingredients such as cement make permeable concrete, coarse aggregate, water and little sand or no sand, make permeable concrete. The intensity of permeable concrete is low when compared to normal concrete. So, permeable concrete is normally used for pedestrian walls, residential streets and parking areas. In order to increase the intensity, we introduce bitumen coated bamboo rods as reinforcement. When compared to steel, bamboo is more efficient in cost and eco-friendly. By using this, we can increase the intensity and compressive strength of permeable concrete.